ANALISIS RESEPSI PERAN GENDER TERHADAP PASANGAN SUAMI ISTRI MUDA DI SIDOARJO PADA FILM BABY BLUES (2022) (The Commercium, 2023)
The issue of inequality experienced by wives is still a polemic in various countries, including Indonesia. Inequality experienced by wives even arises from the smallest scope, namely the family to the community environment. The film Baby Blues (2022) tells how a young mother is discriminated against because of the influence of tradition, which causes the main character to suffer from a mental illness known as baby blues. This study aims to find out how informants interpret the film Baby Blues (2022) regarding inequality in the role of the wife. This research is a qualitative research using reception analysis research method. The collection of data obtained through in-depth interviews with eight informants who are married couples of productive age and live in Sidoarjo. Interview data were validated using source triangulation. The results of this study indicate that as many as two informants are in the dominant or hegemonic acceptance, six informants are in the acceptance of negotiations and no informants are in the opposition category. The difference in acceptance was due to the various experiences, understanding and education of the informants.